- #1

- 3

- 0

Hello,

Here is my example, could you please check and correct if it needed.

[itex]\stackrel{lim}{n\rightarrow ∞}\frac{\sqrt{4n^3+1}-\sqrt[3] {n+2}}{\sqrt[3] {n^6+27}+n}=[/itex] [itex]\stackrel{lim}{n\rightarrow ∞}\frac{\sqrt{4n^3}}{n\sqrt[3] {n^6}}=[/itex][itex]\stackrel{lim}{n\rightarrow ∞}{\frac{{{4n}^\frac{3}{2}}}{n^2}}={{4}^\frac{3}{4}}[/itex]

Thank you!

Here is my example, could you please check and correct if it needed.

[itex]\stackrel{lim}{n\rightarrow ∞}\frac{\sqrt{4n^3+1}-\sqrt[3] {n+2}}{\sqrt[3] {n^6+27}+n}=[/itex] [itex]\stackrel{lim}{n\rightarrow ∞}\frac{\sqrt{4n^3}}{n\sqrt[3] {n^6}}=[/itex][itex]\stackrel{lim}{n\rightarrow ∞}{\frac{{{4n}^\frac{3}{2}}}{n^2}}={{4}^\frac{3}{4}}[/itex]

Thank you!

Last edited: